Selective even-numbered bromination of triptycene tris(thiadiazoles) - Kohl, Bernd; Over, Lena Charlotte; Lohr, Thorsten; Vasylyeva, Mariya; Rominger, Frank; Mastalerz, Michael (Organic letters, 2014)
An unusual even-numbered bromination of triptycene tristhiadiazole is described, giving selectively dibromo-, tetrabromo-, and hexabromotriptycenes with two bromines each at the same phenyl ring. The new compounds can be used as precursors for extended π-conjugated systems and polymers.
Gesehen am 01.12.2020